The 2024 European Society of Cardiology Guidelines for Diagnosis and Management of Atrial Fibrillation: A Viewpoint from a Practicing Clinician's Perspective - Potpara, Tatjana; Romiti, Giulio F.; Sohns, Christian (Thrombosis and Haemostasis, 2024)
Atrial fibrillation (AF) is a complex disease requiring a multidomain and (usually) long-term management, thus posing a significant burden to patients with AF, practitioners, and health care system. Unlike cardiovascular conditions with a narrow referral pathway (e.g., acute coronary syndrome), AF may be first detected by a wide range of specialties (often noncardiology) or a general practitioner. Since timely initiated optimal management is essential for the prevention of AF-related complications, a concise and simple guidance is essential for practitioners managing AF patients, regardless of their specialty. Guideline-adherent management of patients with AF has been shown to translate to improved patient outcomes compared with guideline-nonadherent treatment. To facilitate guideline implementation in routine clinical practice, a good guideline document on AF should introduce only evidence-based new recommendations, while avoiding arbitrary changes, which may be confusing to practitioners. Herein, we discuss the main changes in the 2024 European Society of Cardiology (ESC) AF Guidelines relative to the previous 2020 ESC document. Whether the updates and new recommendations issued by the new guidelines will translate in high adherence in clinical practice (and hence improved prognosis of patients with AF) will need to be addressed in upcoming years.
Keywords: atrial fibrillation; guidelines; evidence-based recommendation